Best Design for Courtyard Occupied Using Computer - Abdul Satar Abdul Latif; Abdul Khalil; Alyaa Abdul Majeed Haleem (Al-Rafidain Journal of Computer Sciences and Mathematics)
The courtyard occupied a great importance in the architectural constructions in olden times and recently, especially in the Arab and Islamic architecture, due to their large atmospheric benefits. In addition to the beauty which they add to these constructions especially in the hot and dry regions nevertheless, the sun has its large effects, +ve and –ve onto the atmosphere of these courtyards and then onto these constructions, and that obligates the architect to do a very complicated calculations and to keep on recalculating to determine these effects, and then to take into account in his design in order to reach the best design. For this reason, it is to be necessary to obtain a mechanical procedure, which enables the designer (the architect) to get the inclusion of these calculations quickly and precisely in order to save the effort, time and expense. The system, which has been built, achieved these calculations quickly and precisely. This system includes a group of units which belong to a main menu to enable the user using it easily in order to obtain its calculation without a need for a perfect knowledge about (using) computer. Baghdad City has been selected as a pattern of geographical site in which the courtyard is situated.